Sistematización de los saberes sobre los animales pronosticadores de la cultura achuar para complementar y enriquecer los contenidos del área de ciencias sociales - Chayat Kayap, Chumap Ramón (2018)
In the Achuar people, the predictive animals are a value of our experiences, beliefs and wisdoms that come to be complex strategies for children who learn to know and understand which are the animals that announce the death of family and foreigners. However, counting on the degree of maturity determined and with a favorable educational environment, children are able to know their own cultural aspect. In today's life, now, all children, young ladies and young people, in reality, do not have values of culture, but rather they want to copy other ethnicities from another culture. Teachers at the time of teaching learning reach to teach counting the ancestral cultural reality in other aspects also; the present research is based on an educational experience carried out in three communities: Tsunkintsa, Ikiam and Saum, which is of great importance in my life. I carried out an investigation about the systematization of knowledge about the prognostic animals of the Achuar culture to complement and enrich the contents of the Social Sciences area. In the Achuar people, in today's life, most of the elderly almost do not have these experiences about the animals that announce death, in fact, the Achuar nationality is at that risk; Many young people, young ladies and parents of families want to live in the city, for that reason they forget their culture, however, the teachers must teach about the cultures of the nationalities to the children.